Crystal size effect in two dimensions – Influence of size and shape. (June 2015) - Maaß, R.; Volkert, C.A.; Derlet, P.M.
Abstract : Based on the statistics of both the stress and strain of a plastic event, the well known size-effect in strength can be linked to a crystal's critical stress distribution and the universal scaling exponent of intermittent plasticity. We successfully test these hypotheses with small-scale deformation experiments as a function of diameter and aspect ratio, and find that the latter affects the material's strength in a way that gives direct insight into the underlying critical stress distribution of the deforming volume.